Analisis Forecasting Dan Keputusan Manajemen : Teori & Aplikasi Metode Analisis Kuantitatif - SOEPARNO. W (Salemba Empat, 2009)
Analisis Forecasting Dan Keputusan Manajemen : Teori & Aplikasi Metode ...